Long-run Price Performance Phenomenon of Initial Public Offerings: A Review of Theoretical and Empirical Perspectives - Gurung, Jas Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
This article focuses on reviewing, discussing, and synthesizing the literature on the long-run price performance of initial public offerings. The systematic review was assumed to review articles published between 1990 and 2023. The author developed an inclusive framework and suggested an upcoming research agenda found in their discussion. This comprehensive overview of IPO’s long-run performance can be an interesting document for Nepali scholars as well as scholars of the global academic community. To the best of the author’s knowledge, this is the pioneer comprehensive review paper that reviews, synthesizes, and drafts the imminent research agenda. This review can be appropriate for researchers, policymakers, finance professionals, and anyone else interested in the Nepali IPO market. Bibliometric and PRISM methodologies of the literature can be employed to gain a better understanding of the findings of prior studies in the future.